Elucidating early proton irradiation effects in metal halide perovskites via photoluminescence spectroscopy - Samuel Erickson; Calista Lum; Katie Stephens; Mritunjaya Parashar; Darshpreet Kaur Saini; Bibhudutta Rout; Cheol Park; Timothy J. Peshek; Lyndsey McMillon-Brown; Sayantani Ghosh (iScience)
Summary: Metal halide perovskite (MHP) solar cells are promising aerospace power sources given their potential as inexpensive, lightweight, and resilient solar electricity generators. Herein, the intrinsic radiation tolerance of unencapsulated methylammonium lead iodide/chloride (CH3NH3PbI3-xClx) films was isolated. Spatially resolved photoluminescence (PL) spectroscopy and confocal microscopy revealed the fundamental defect physics through optical changes as films were irradiated with 4.5 MeV neutrons and 20 keV protons at fluences between 5×1010 and 1×1016 p+/cm2. As proton radiation increased beyond 1×1013 p+/cm2, defects formed in the film, causing both a decrease in photoluminescence intensity and a 30% increase in surface darkening. All proton irradiated films additionally exhibited continuous increase of energy bandgaps and decreasing charge recombination lifetimes with increasing proton fluences. These optical changes in the absorber layer precede performance declines detectable in standard current-voltage measurements of complete solar cell devices and therefore have the potential of serving as early indicators of radiation tolerance.